Digital Brotherhood: Group Identity, In Group Bias, and Behavioral Conformity in Bandung’s Esports Communities - Evarianisa (Indonesian Scientific Publication, 2025)
The rapid rise of esports in urban Indonesia has reshaped youth culture and identity, particularly in Bandung, where digital teams act as important spaces for collective belonging. This study investigates how group identity influences in-group bias and behavioral conformity among esports gamers. Using a mixed methods approach combining a survey of 150 players and in-depth interviews with 15 participants, supported by observations at local tournaments, the research revealed that stronger group identity was significantly associated with higher conformity to team norms and stronger favoritism toward in-group members. Qualitative narratives further showed that symbolic markers such as jerseys and team tags, emotional loyalty, and peer-enforced rules play a crucial role in shaping behaviors and reinforcing cohesion both online and offline. These findings highlight that esports communities serve not only as entertainment hubs but also as arenas for identity formation and social learning, suggesting the need for educational and youth development frameworks that recognize the psychosocial value of digital gaming cultures.